296_pdfsam_math 54 differential equation solutions odd

296_pdfsam_math 54 differential equation solutions odd -...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 5 Here f1 (t, x1 , x2 , x3 ) = x2 , f2 (t, x1 , x2 , x3 ) = x3 , f3 (t, x1 , x2 , x3 ) = t − x3 − x2 . 1 Since we are computing the approximations for c = 1, the initial value for h in Step 1 of the algorithm in Appendix E of the text is h = (1 − 0)2−0 = 1. The equations in Step 3 are k1,1 = hf1 (t, x1 , x2 , x3 ) = hx2 , k2,1 = hf2 (t, x1 , x2 , x3 ) = hx3 , k3,1 = hf3 (t, x1 , x2 , x3 ) = h t − x3 − x2 , 1 k1,1 k2,1 h k1,2 = hf1 t + , x1 + , x2 + , x3 + 2 2 2 k1,1 k2,1 h , x2 + , x3 + k2,2 = hf2 t + , x1 + 2 2 2 k3,1 2 k3,1 2 k2,1 , 2 k3,1 = h x3 + , 2 = h x2 + =h t+ k3,1 k1,1 h − x3 − − x1 + 2 2 2 2 k1,1 k2,1 k3,1 h , x2 + , x3 + k3,2 = hf3 t + , x1 + 2 2 2 2 h k1,3 = hf1 t + , x1 + 2 h k2,3 = hf2 t + , x1 + 2 k3,3 = hf3 k1,2 , x2 + 2 k1,2 , x2 + 2 k2,2 , x3 + 2 k2,2 , x3 + 2 k3,2 2 k3,2 2 , k2,2 , 2 k3,2 = h x3 + , 2 = h x2 + k3,2 k1,2 h − x1 + = h t + − x3 − 2 2 2 2 k1,2 k2,2 k3,2 h , x2 + , x3 + t + , x1 + 2 2 2 2 , k1,4 = hf1 (t + h, x1 + k1,3 , x2 + k2,3 , x3 + k3,3 ) = h (x2 + k2,3 ) , k2,4 = hf2 (t + h, x1 + k1,3 , x2 + k2,3 , x3 + k3,3 ) = h (x3 + k3,3 ) , k3,4 = hf3 (t + h, x1 + k1,3 , x2 + k2,3 , x3 + k3,3 ) = h t + h − x3 − k3,3 − (x1 + k1,3 )2 . Using the starting values t0 = 0, a1 = 1, a2 = 0, and a3 = 1, we obtain the first approximations x1 (1; 1) = 1.29167 , x2 (1; 1) = 0.28125 , 292 ...
View Full Document

This note was uploaded on 03/29/2010 for the course MATH 54257 taught by Professor Hald,oh during the Spring '10 term at University of California, Berkeley.

Ask a homework question - tutors are online